Investigating a Dual Degrader Strategy for Targeted ALK-Positive Cancer Therapy and Immune Activation - Panting, Daniel (Université d'Ottawa | University of Ottawa, 2026)
Constitutively active anaplastic lymphoma kinase (ALK) drives a variety of cancers. Although ALK inhibitors are clinically effective, resistance frequently emerges, leading to poor patient outcomes. Proteolysis-targeting chimeras (PROTACs) represent an alternative strategy that degrades ALK rather than inhibiting it. PROTACs function by recruiting an E3 ligase to trigger proteasomal degradation of their targets. This study evaluates novel ALK-targeting PROTACs that recruit anti-apoptotic and immunomodulatory Inhibitor of Apoptosis (IAP) proteins, thereby degrading ALK and providing anti-ALK tumor and pro-immunostimulatory effects. Novel PROTAC compounds were ranked based on their ALK degradation properties using a high-throughput AlphaLISA screen. The anti-ALK and IAP effects of the top compounds were examined using Western blotting, live microscopy, and viability assays in cancer cell lines. The effects of these PROTACs on immune cells were studied using macrophages and dendritic cells. Lead PROTACs induced potent degradation of both ALK and IAPs. Treatment reduced proliferation and increased cell death in ALK-positive cancer cells. Additionally, DCs treated with library compounds exhibited enhanced expression of maturation markers. These findings highlight the therapeutic potential of IAP-based PROTACs that induce direct ALK degradation and activate anti-tumour immunity via IAP depletion. This work establishes a foundation for developing next-generation PROTAC therapeutics for ALK-driven cancers and builds on evidence supporting their promising future.
Keywords: ALK; Cancer; Proteolysis